Hydrophilic molecularly imprinted phenol-amine-formaldehyde resins - Yuliya Yu. Petrova; Elena V. Bulatova; Dmitry O. Zelentsov; Yuliya G. Mateyshina (Chimica Techno Acta)
Hydrophilic molecularly imprinted resins (MIR), which are produced using hydrophilic monomers such as phenols, aldehydes, melamine or urea, have recently attracted increasing attention for use in separation and preconcentration. Among their obvious advantages are good sorption capacity, high recovery and selectivity, as well as their reusability in aqueous solutions. In this work we applied the bulk molecular imprinting method to produce quercetin-imprinted phenol-amino-formaldehyde resin. For this purpose, phloroglucinol and melamine solutions were mixed with formaldehyde and then polyethylene glycol and quercetin (Qu) were added to the obtained solution as a porogen and a template, respectively. The mixture was stirred under heating, then left in the thermostat for a continuous time. The optimum ratio of phloroglucinol to melamine was 3:1. The average molecular mass of porogen (Mw) varied between 4000–10000 Da. The obtained MIR were eluted with ethanol-water mixture (4:1, v/v) in the Soxhlet extractor for 36 h to remove the template. The MIR were characterized by FTIR-spectroscopy, laser diffraction spectroscopy and differential thermal analysis. The maximum recovery and sorption capacity of MIR synthesized in the presence of a porogen with Mw 10000 were 47% and 4.7 μmol Qu/g, respectively. The maximum imprinting factor was 1.41. The sorption kinetics of quercetin by a non-imprinted resin (NIR) is best described by a pseudo-second-order model, while MIR has a mixed pseudo-first-second-order mechanism.